Ablation behavior of Ti6Al4V in laser micro machining process. Issue 169 (12th February 2016) - Wang, Chuanjie; Chen, Gang; Luan, Dong; Zhang, Peng
Abstract: The effect of laser irradiation time and laser power on the laser ablation behavior of Ti6Al4V is studied experimentally in the study. It is indicated that the contents of the elements are varied with the locations after laser irradiation. The irradiated region by the laser is segmented into two parts (the laser ablation and heat-affected regions) by two circles. The radii of the inner and outer circles increase with the laser irradiation time for all the laser powers and reach to a stable value of the laser beam radius, respectively. Then the ablation mechanism of the Ti6Al4V is revealed according to the Gaussian distribution of laser beam.